Uncertainty and correlation analysis of lead nuclear data on reactor parameters for the European Lead Cooled Training Reactor. (January 2015) - Alhassan, E.; Sjöstrand, H.; Helgesson, P.; Koning, A.J.; Österlund, M.; Pomp, S.; Rochman, D.
Highlights: The impact of lead nuclear data uncertainties on reactor parameters was investigated. Cross section-parameter correlations as a function of energy were also studied. Dominant contributions to the uncertainty in k eff came from 208 Pb nuclear data. Abstract: The Total Monte Carlo (TMC) method was used in this study to assess the impact of 204, 206, 207, 208 Pb nuclear data uncertainties on reactor safety parameters for the ELECTRA reactor. Relatively large uncertainties were observed in the k eff and the coolant void worth ( CVW ) for all isotopes except for 204 Pb with significant contribution coming from 208 Pb nuclear data; the dominant effect came from uncertainties in the resonance parameters; however, elastic scattering cross section and the angular distributions also had significant impact. It was also observed that the k eff distribution for 206, 207, 208 Pb deviates from a Gaussian distribution with tails in the high k eff region. An uncertainty of 0.9% on the k eff and 3.3% for the CVW due to lead nuclear data were obtained. As part of the work, cross section-reactor parameter correlations were also studied using a Monte Carlo sensitivity method. Strong correlations were observed between the k eff and (n, el) cross section for all the lead isotopes. The correlation between the (n, inl) and the k eff was also found to be significant.